Representaciones en quechua de los conceptos de descanso, barbecho y fertilidad del suelo - Godenzzi, Juan Carlos (1998)
In his linguistic and socio-cultural activity, the human being attempts to make sense of his relationship with the world at large. His representation of the world is linked to his language in two ways: nor only instrumental by conditioning the way we think, but also by creating some of our conceptual organizational outlines of the Universe. We have analyzed texts from Colonial Quechua authors, in addition to contemporary testimonies concerning the fertility of the soil. The connotations and figures of speech employed in the representation of the concepts of rest, fallow and soil fertility presume a reciprocal relationship between the soil and the environment, which are considered as living beings. In this way, agricultural activities -their space, time and social interactions- are not always organized in a manner that is understandable in terms of modern development.